2002
DOI: 10.1177/0075424202025004601
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Air Pressure Response of Multizonal Buildings

Abstract: Air flow in buildings is a complex flow and pressure distribution problem that makes quantification difficult. However, certain parameters have recently become easy to quantify – specifically the air pressure relationships within buildings. The measured building air pressure field can be used with network analysis to solve the building flow and leakage regime creating an analytical macro model of the building flow and leakage regime. The response of the analytical model can be further tuned by perturbing both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Only recently in Scandinavia and North America the focus shifted to frame walls and included effects of air flow. It was found that air flows carry more moisture than water vapor diffusion, and that air, in a manner similar to sound transmission, flowing across and along building partitions, may connect seemingly separate regions of the building (Lstiburek, 2000;Lstiburek et al, 2000 and2002). Furthermore, moisture carried by air is a major factor affecting durability of building materials.…”
Section: Effect Of Thermal Bridgesmentioning
confidence: 99%
“…Only recently in Scandinavia and North America the focus shifted to frame walls and included effects of air flow. It was found that air flows carry more moisture than water vapor diffusion, and that air, in a manner similar to sound transmission, flowing across and along building partitions, may connect seemingly separate regions of the building (Lstiburek, 2000;Lstiburek et al, 2000 and2002). Furthermore, moisture carried by air is a major factor affecting durability of building materials.…”
Section: Effect Of Thermal Bridgesmentioning
confidence: 99%
“…Assuming that all pressure boundaries have the same n value, C values for each zone boundary can be determined using the BDT data. This technique has also been used to aid in calibration of airflow network models 176‐178 . More recently, Gray adapted the perturbation method to isolate exterior and interior air leakage rates at the suite‐level in MURBs 179 .…”
Section: Test Methodsmentioning
confidence: 99%
“…This technique has also been used to aid in calibration of airflow network models. [176][177][178] More recently, Gray adapted the perturbation method to isolate exterior and interior air leakage rates at the suite-level in MURBs. 179 Unfortunately, the changes in pressure induced by the perturbation were often lower than the wind-induced pressures and the results showed poor agreement with guarded BDT.…”
Section: Perturbationmentioning
confidence: 99%
“…The effect of pathways created by external cavities and interconnected internal cavities communicating with HVAC systems on performance of building systems is often neglected (Figure 4). The significance of these elements has been illustrated in the few examples selected from case studies (Lstiburek, 1995, 2002, Lstiburek et al, 2000. Some other cases listed by Lstiburek (1998) are as follows: A facility located in a cold climate with inadequate provision for return air.…”
Section: Need For Testing Airtightnessmentioning
confidence: 99%